2013
DOI: 10.1155/2013/741403
|View full text |Cite
|
Sign up to set email alerts
|

Moving toward Personalized Medicine in the Methadone Maintenance Treatment Program: A Pilot Study on the Evaluation of Treatment Responses in Taiwan

Abstract: This pilot study simultaneously evaluated the effects of various factors, including genetic variations of CYP2B6, CYP2C19, and ABCB1, demographic characteristics, disease states, methadone-drug interactions (MDIs), and poly-substance use, on the treatment responses among non-HIV patients in the methadone maintenance treatment program (MMTP) in Taiwan. A total of 178 patients were recruited from two major hospitals that provided MMTP services in southern Taiwan, and information regarding concomitant medications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…Pharmacokinetic status of family members such as CYP2B6 and CYP3A4 have been associated with plasma concentrations of methadone but connections to dose requirements have been more equivocal 7, 1114 . Genotypes at ABCB1 , a gene encoding a transmembrane efflux pump, have also been linked to methadone serum levels and dose 1517 . As with the CYP genes, a number of studies have failed to replicate the ABCB1 associations with dose (reviewed in 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacokinetic status of family members such as CYP2B6 and CYP3A4 have been associated with plasma concentrations of methadone but connections to dose requirements have been more equivocal 7, 1114 . Genotypes at ABCB1 , a gene encoding a transmembrane efflux pump, have also been linked to methadone serum levels and dose 1517 . As with the CYP genes, a number of studies have failed to replicate the ABCB1 associations with dose (reviewed in 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…In their 2018 review, Fonseca and Torrens highlighted the influence of CYP2B6 , and to some extent CYP2D6 and CYP2C19 , genetic variability on methadone pharmacokinetics . Three studies described in that review reported that the CYP2B6 gene had no influence on the methadone response.…”
Section: Discussionmentioning
confidence: 99%
“…A Swiss study of 14 MMT subjects found the ABCB1 genotypes 3435 TT, CT, and CC resulted in 3, 23 and 33% increases in (R)-methadone concentration/dose ratios following administration of P-gp substrate quetiapine, respectively (158). Carriers of the variant ABCB1 3435C>T were found to require higher doses of methadone than non-carriers among a population of Han Chinese patients (157), and a pilot study of 178 Taiwanese patients in a MMT program found the ABCB1 2677T allele had positive effects on methadone plasma concentration (159).…”
Section: Methadonementioning
confidence: 99%
“…Some clinical studies have suggested there is a likely relationship (155)(156)(157)(158)(159), while others have suggested there is likely not (161)(162)(163)165), and still others propose that ABCB1 polymorphisms are only one of a number of interacting pharmacogenetic determinants influencing methadone pharmacokinetics (160). Despite extensive research, there remains considerable controversy over the functional consequences of various ABCB1 polymorphisms (222)(223)(224)(225).…”
Section: Methadonementioning
confidence: 99%